2009
DOI: 10.1108/00346650910930806
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of the risk of overweight and overweight among Qatari children ages 9 through 11

Abstract: PurposeThe purpose of this paper is to estimate the prevalence of the risk of overweight and overweight in Qatari children ages 9 through 11 and to compare the prevalence using CDC and IOTF cut‐offs.Design/methodology/approachA cross‐sectional study in a randomly selected sample of 1,213 Qatari children was carried out. Weight and height were measured and BMI was calculated for all children. The risk of overweight and overweight were defined using as references both the CDC BMI percentiles for age and gender a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…The results of this study are similar to those of a recent study by Kerkadi et al, which reported a prevalence of overweight and obesity by age of 33.2%, 33.5%, and 44.7% for boys and 37.0%, 38.9% and 43.3% for girls aged 9, 10, and 11 years using IOTF references, respectively 15. Other studies among adolescents in Qatar report a high risk of overweight and obesity 14.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of this study are similar to those of a recent study by Kerkadi et al, which reported a prevalence of overweight and obesity by age of 33.2%, 33.5%, and 44.7% for boys and 37.0%, 38.9% and 43.3% for girls aged 9, 10, and 11 years using IOTF references, respectively 15. Other studies among adolescents in Qatar report a high risk of overweight and obesity 14.…”
Section: Discussionsupporting
confidence: 90%
“…To date, there are currently no data evaluating cardiovascular risk in terms of associations of overweight and obesity with the lipid profile and intra-abdominal fat assessed by waist circumference among Qatari schoolchildren. Several recent studies have addressed the prevalence of pediatric obesity in Qatar without addressing its association with important health issues, such as development of cardiovascular disease in adulthood 1315. This study extends our recent work, which has demonstrated a significant prevalence of metabolic syndrome and its associated features among overweight and obese children 16.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…In addition, obesity in childhood frequently tracks into adulthood [13,18]. Childhood obesity and overweight is common in children and adolescents in Qatar [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The young population is extremely affected, as well. A cross sectional study of 1213 Qatari children (683 girls and 530 boys) aged 9-11 years old showed that the prevalence of overweight and obesity affected 21.1% and 17.7%, respectively [22]. In another study, Bener and Kamal [23] reported that the overall prevalence of overweight and obesity among children and adolescents was 19.8% and 4.3%, respectively [23].…”
Section: Obesity In Qatarmentioning
confidence: 99%